Cytotoxic effects and comparative analysis of Ni ion uptake by osteoarthritic and physiological osteoblasts - Navratilova, Polina; Vejvodova, Marketa; Vaculovic, Tomas; Slaninova, Iva; Emmer, Jan; Tomas, Tomas; Ryba, Ludek; Burda, Jan; Pavkova Goldbergova, Monika (Scientific reports, 2024)
Nickel(Ni)-containing materials have been widely used in a wide range of medical applications, including orthopaedics. Despite their excellent properties, there is still a problem with the release of nickel ions into the patient's body, which can cause changes in the behaviour of surrounding cells and tissues. This study aims to evaluate the effects of Ni on bone cells with an emphasis on the determination of Ni localization in cellular compartments in time. For these purposes, one of the most suitable models for studying the effects induced by metal implants was used-the patient's osteoarthritic cells. Thanks to this it was possible to simulate the pathophysiological conditions in the patient's body, as well as to evaluate the response of the cells which come into direct contact with the material after the implantation of the joint replacement. The largest differences in cell viability, proliferation and cell cycle changes occurred between Ni 0.5 mM and 1 mM concentrations. Time-dependent localization of Ni in cells showed that there is a continuous transport of Ni ions between the nucleus and the cytoplasm, as well as between the cell and the environment. Moreover, osteoarthritic osteoblasts showed faster changes in concentration and ability to accumulate more Ni, especially in the nucleus, than physiological osteoblasts. The differences in Ni accumulation process explains the higher sensitivity of patient osteoblasts to Ni and may be crucial in further studies of implant-derived cytotoxic effects.
Keywords: kultivované buňky; osteoartróza; Cells, Cultured; osteoblasty; Cell Proliferation; Implant debris; lidé; Humans; Nickel; Metal distribution; Cell Cycle; proliferace buněk; nikl; viabilita buněk; buněčný cyklus; Laser ablation; Osteoblasts; Osteoarthritis; Metal uptake; ionty; Cell Survival; Ions